Empowering staff to improve processes according to European quality standards (EFQM) - عبد الرضا, نغم يوسف (Journal of Economics and Administrative Sciences, 2019)
The research dealt with two variables first in the field of human resources represented by the empowerment of workers  and second in operations through improved process in the framework of standards Quality Award European containing nine basic criteria (Leadership, Strategy, partnerships and resources, the results of the individuals, the results of the customer, the results of the community), including human resources and operations has been selected and the Ministry of Industry and Minerals as a community to search , which covered most of the industrial sectors of Iraq through the selection of a single company of every industrial sector and thus became the research sample (6 ) industrial companies in addition to the Center of the Ministry of Industry and Minerals through ( 90 ) employees working in the departments of Central and production lines has been used for this purpose, a questionnaire was designed based on a scale ( Fif ) for first variable while the designing a measure of the second variable was presented to a group of experts in the field of competence in the use of a number of statistical techniques ( correlation , regression , the mean and standard deviation ) for the purpose of testing hypotheses research has come to a set of conclusions , including the lack of balance between the size of the responsibilities of employees and powers granted to them and this lead to the second conclusion , a lack of expansion in the granting of powers to the workers limiting their ability to make the right decision for a certain position in a timely manner and was directing a general set of recommendations to the companies surveyed for the purpose of addressing the current situation , including the expansion of the granting of powers and increase awareness and education towards progress toward European quality standards for other areas .